Economy-related risks interpretation and classification - Бойко, Тарас Георгійович (Technology audit and production reserves, 2014)
Based on the analysis of the requirements of legal acts and regulations of Ukraine for Technical Regulation, the need for a differentiated approach to assessing the belonging of the evaluation object, which may be an enterprise, type of economic activity or enterprise products to the risk groups is shown. The essence of the term "risk" and corresponding closely-related concepts was analyzed, their unambiguous interpretation for referring economic entities to the risk groups, which take into account adverse effects, caused by economic activities, is proposed. The division criteria and classification of economy-related risks for grading economic entities and their products according to the risk levels are proposed. It is concluded that it is advisable to systemize, classify and specify the presented types of risks for each economic entity and its economic objects as an important component that has a significant impact on its activity in general and the life cycle of its products.